Newly described salivary gland tumors - Skalova, Alena; Michal, Michal; Simpson, Roderick Hw (Modern pathology, 2017)
This review concentrates on three salivary gland tumors that have been accepted in the recent literature as new neoplastic entities: mammary analog secretory carcinoma (MASC), sclerosing polycystic adenoma (SPA) and cribriform adenocarcinoma of tongue and other minor salivary glands (CAMSGs). MASC is a distinctive low-grade malignant salivary cancer that harbors a characteristic chromosomal translocation, t(12;15) (p13;q25) resulting in an ETV6-NTRK3 fusion. SPA is a rare lesion often mistaken histologically for low-grade salivary carcinoma. Previously thought to be a reactive fibroinflammatory process, but recent evidence of clonality, recurrences in up 30%, and dysplastic foci suggest it may be truly neoplastic. CAMSG is a distinct tumor entity that differs from polymorphous low-grade adenocarcinoma (PLGA) by location (ie, most often arising on the tongue), by prominent nuclear clearing, alterations of the PRKD gene family and clinical behavior with frequent metastases at the time of presentation of the primary tumor. Early metastatic disease seen in most cases of CAMSG associated with indolent behavior makes it a unique neoplasm among all low-grade salivary gland tumors. Salivary glands may give rise to a wide spectrum of different tumors. They are often diagnostically challenging as morphological features often overlap between different entities. Although conventional morphology in combination with immunohistochemical findings still provide the most important clues for diagnosis, recent advances in molecular pathology offer new diagnostic tools in investigating the differential diagnosis, as well as providing potentially valuable prognostic indicators. In the last two decades, several new salivary gland tumor entities have been described, namely MASC, SPA and CAMSGs.
Keywords: prognóza; Mammary Analogue Secretory Carcinoma; Prognosis; adenom; sekreční karcinom mamárního typu; Oncogene Proteins, Fusion; Adenocarcinoma; lidé; Salivary Gland Neoplasms; nádory slinných žláz; fúzní onkogenní proteiny; Biomarkers, Tumor; adenokarcinom; Humans; nádorové biomarkery; Adenoma